1991
DOI: 10.1182/blood.v77.12.2655.bloodjournal77122655
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to platelets in patients with anti-phospholipid antibodies

Abstract: Binding of anti-phospholipid antibodies to circulating platelets and its consequences on platelet activation and aggregation was investigated in 11 patients with anti-phospholipid antibodies. Seven patients had mild thrombocytopenia. Nine healthy donors served as controls. Binding to platelets was investigated by performing enzyme- linked immunosorbent assays (ELISAs) with phospholipids as antigen on platelet eluates. Platelet activation was measured by flow cytofluorometry using monoclonal antibodies to an ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…APL antibodies also induce platelet activation and interact with elements of the coagulation cascade. 8,9,[10][11][12][13][14][15] This activity, however, does not seem to be sufficient to cause thrombosis. Activation of the complement cascade by aPL may amplify these effects by stimulation of the generation of potent mediators of platelet and endothelial cell activation, including C3a and C5a and the C5b-MAC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…APL antibodies also induce platelet activation and interact with elements of the coagulation cascade. 8,9,[10][11][12][13][14][15] This activity, however, does not seem to be sufficient to cause thrombosis. Activation of the complement cascade by aPL may amplify these effects by stimulation of the generation of potent mediators of platelet and endothelial cell activation, including C3a and C5a and the C5b-MAC.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 In fact, in vitro studies have reported that aPL may cause thrombosis by interfering with activation of protein C (or inactivation of factor V by activated protein C), inhibit endothelial prostacyclin production, impair fibrinolysis, and exert stimulatory effect on platelet function. [6][7][8][9][10][11][12][13][14][15][16][17][18][19] Recently convincing evidence has shown that activation of complement mediates thrombogenic effects of aPL and fetal loss in APS. [20][21][22][23][24] This paper discusses specifically those new and exciting findings with respect to the involvement of the complement cascade in pathogenic effects of aPL antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Elsewhere, an imbalance between the synthesis of thromboxane and prostaglandin I 2 has been reported in patients with lupus anticoagulant ( Lellouche et al , 1991 ). Other studies have failed to confirm that platelets circulate in an activated state in patients who display platelet binding anti‐phospholipid antibodies ( Out et al , 1991 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that platelet microparticles and activated platelets are present in the circulation in certain thrombotic disease states ( Abrams et al , 1990 ; Michelson, 1996), as well as in patients with antiphospholipid antibodies ( Galli et al , 1993b ). Some recent studies, using flow cytometry to detect the expression of platelet activation markers, have indicated that patients with the antiphospholipid syndrome have circulating activated platelets ( Fanelli et al , 1997 ; Galli et al , 1993b ; Joseph et al , 1997 ), although this has not been a consistent finding ( Out et al , 1991 ). It is unclear, however, whether ‘antiphospholipid’ antibodies are capable of initiating platelet activation, or if other components and conditions are required.…”
mentioning
confidence: 99%
“…It is commonly used in the diagnosis of clinical conditions such as acute leukaemia and human immunodeficiency virus. Its versatility as a tool for identification of cell surface antigens has also enabled the study of antiplatelet antibodies (11). Monoclonal antibodies have been used to identify platelet activation in immune thrombocytopaenia (12,13), as well as in patients following cardiopulmonary bypass and in hypercoagulable states (14)(15)(16).…”
mentioning
confidence: 99%